Association of open communication and the emotional and behavioural impact of medical error on patients and families: state-wide cross-sectional survey. Issue 11 (20th January 2020) - Prentice, Julia C; Bell, Sigall K; Thomas, Eric J; Schneider, Eric C; Weingart, Saul N; Weissman, Joel S; Schlesinger, Mark J
Abstract : Background: How openly healthcare providers communicate after a medical error may influence long-term impacts. We sought to understand whether greater open communication is associated with fewer persisting emotional impacts, healthcare avoidance and loss of trust. Methods: Cross-sectional 2018 recontact survey assessing experience with medical error in a 2017 random digit dial survey of Massachusetts residents. Two hundred and fifty-three respondents self-reported medical error. Respondents were similar to non-respondents in sociodemographics confirming minimal response bias. Time since error was categorised as <1, 1–2 or 3–6 years before interview. Open communication was measured with six questions assessing different communication elements. Persistent impacts included emotional (eg, sadness, anger), healthcare avoidance (specific providers or all medical care) and loss of trust in healthcare. Logistic regressions examined the association between open communication and long-term impacts. Results: Of respondents self-reporting a medical error 3–6 years ago, 51% reported at least one current emotional impact; 57% reported avoiding doctor/facilities involved in error; 67% reported loss of trust. Open communication varied: 34% reported no communication and 24% reported ≥5 elements. Controlling for error severity, respondents reporting the most open communication had significantly lower odds of persisting sadness (OR=0.17, 95% CI 0.05 to 0.60, p=0.006), depression (OR=0.16, 95% CI 0.03 to 0.77, p=0.022) or feeling abandoned/betrayed (OR=0.10, 95% CI 0.02 to 0.48, p=0.004) compared with respondents reporting no communication. Open communication significantly predicted less doctor/facility avoidance, but was not associated with medical care avoidance or healthcare trust. Conclusions: Negative emotional impacts from medical error can persist for years. Open communication is associated with reduced emotional impacts and decreased avoidance of doctors/facilities involved in the error. Communication and resolution programmes could facilitate transparent conversations and reduce some of the negative impacts of medical error.